Determination of Pb(II) and Cr(VI) using gold nanoparticles and ionophore-modified screen printed electrode - Tukur, Salamatu Aliyu (2014)
In this research, gold nanoparticles (AuNPs) was prepared and used as modifier for disposable screen printed electrodes (SPE). The AuNPs was characterized by different spectroscopic techniques; prior to application on surface of the electrode to increase the sensitivity of the electrode. The SPE was modified by casting AuNPs onto its surface. The modified electrode (AuNPs/SPE) was applied in Cr(VI) and Pb(II) detection. Linear sweep stripping voltammetry was performed with AuNPs/SPE and it showed better response than the bare SPE. Analysis of chromium with AuNPs/SPE gave two linear calibrations and a lowest detection limit of 1.6 × 10-6 μg L-1 reported to date was achieved by applying deposition potential of -1.1 V and deposition time of 180 s. The electrode also showed very good recovery indicating the accuracy of the method. While concentration study of lead with AuNPs/SPE gave a linear calibration with R2 = 0.990, a detection limit of 1.3 μg L-1 was achieved by applying deposition potential of -1.2 V and deposition time of 240 s. Validation of the method with Inductively coupled plasma-mass spectroscopy (ICP-MS) and Atomic absorption spectroscopy showed very good correlation. AuNPs together with an ionophore was also prepared and used as an electrode. The SPE was modified by casting the AuNPs/Ionophore solution. The AuNPs/ionophore/SPE was used for the analysis of Pb(II) and selective effect of the ionophore towards Pb(II). The ionophore used was found to be selective to lead ion in presence of foreign metal ions. This AuNPs/ionophore/SPE gave a lower LOD of 0.9 μg L-1 which is lower than LOD of 1.3 μg L-1 obtained with AuNPs/SPE. Selectivity study for a mixture of Hg(II) and Cd(II) ions with Pb(II), proves this sensor to be selective towards Pb(II).